Awake Throughout Craniotomy: Initial Experience and the Anaesthetic Challenges - Shakya, Bigen M; Acharya, Binita; Shrestha, Gentle S; Shrestha, Anil; Sedain, Gopal; Shrestha, Ninadini (Journal of Institute of Medicine Nepal, 2019)
The tumor of brain near or within the eloquent brain regions like motor and language cortex requires excision of tumor and at the same time preservation of the functional area. To achieve the second goal the awake craniotomy is being practiced where the aim is to make the patient awake during resection of tumor so that the motor and speech function can be constantly monitored. We present the anaesthetic management of a case of craniotomy for low grade oligodendroma in frontal region with the awake throughout technique.